Host defense against the infection of Klebsiella pneumoniae: New strategy to kill the bacterium in the era of antibiotics? - Liang, Zihan; Wang, Yiyao; Lai, Yixiang; Zhang, Jingyi; Yin, Lanlan; Yu, Xiang; Zhou, Yongqin; Li, Xinzhi; Song, Yinhong (Frontiers in Cellular and Infection Microbiology, 2022)
Klebsiella pneumoniae (K. pneumoniae) is a typical gram-negative iatrogenic bacterium which often causes bacteremia, pneumonia and urinary tract infection particularly among those with low immunity. Although antibiotic treatment is the cornerstone of the infections, the clinical efficacy of β-lactamase and carbapenems drugs has been weakened due to the emergence of drug-resistant K. pneumoniae. Recent studies have demonstrated that self-immune effects play a critical role in the defenses of K. pneumoniae. Here, we summarize our current understanding of the immunity mechanisms against K. pneumoniae, including mechanical barrier, natural immune cells, lymphocytes and humoral immunity, providing a theoretical basis and new strategy for the clinical treatment of K. pneumoniae through strengthening self-immunity.